Integrasi Gamifikasi ke dalam Virtual Reality untuk Mewujudkan Pembelajaran Imersif - Cicilia Ika Mayawati; Evalin Ndoen; Stephanie Anggreinie (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
This research discusses how gamification in Virtual Reality (VR) can be applied to immersive learning. This study uses a descriptive qualitative approach with a literature review. From this study, we describe the various challenges and the solutions with the hope that learning that utilizes this new technology will not only be exciting and can also provide effective learning outcomes. It was found that it was necessary to make adjustments to the equipment, design, and implementation. In terms of equipment, adjustments can be made using cheaper equipment. In design, it is necessary to adjust to the needs of the students and the learning objectives themselves. Then in the implementation, it is essential to make adjustments by providing appropriate stages and ensuring students understand how the context is learned through VR gamification can be realized in the real world.